Analysis Of Disaster Awareness And Preparedness Among Undergraduate Students In Public Health In High Risk Areas Of Urban Disasters - Wulandari, Anis; Palupi, Retno; Purnomo, Windhu (International Journal of Psychosocial Rehabilitation, 2020)
Background: Indonesia geographically has high vulnerability to disasters. Urban areas have high social vulnerability thereby increasing the potential risk of disaster impacts. Students, as youth workers have contributive potential in disaster management. Objective: To analyze awareness and preparedness of undergraduate students of Public Health students. Method: A cross sectional study with 105 respondents of undergraduate students Public Health students. The study was conducted using a questionnaire consisting of 23 questions. Results: There were 94 students (89.50%) women, 59 respondents came from students (56.20%)